Difference between revisions of "1981 AHSME Problems/Problem 24"
Alexwin0806 (talk | contribs) (→Solution) |
Alexwin0806 (talk | contribs) (→Solution) |
||
Line 8: | Line 8: | ||
<cmath>x=\cos(\theta) + \sqrt{\cos^2(\theta)-1}</cmath> | <cmath>x=\cos(\theta) + \sqrt{\cos^2(\theta)-1}</cmath> | ||
− | <cmath>x=\cos(\theta) + \sqrt{(-1)(\sin^2(\theta | + | <cmath>x=\cos(\theta) + \sqrt{(-1)(\sin^2(\theta)}</cmath> |
<cmath>x=\cos(\theta) + i\sin(\theta)</cmath> | <cmath>x=\cos(\theta) + i\sin(\theta)</cmath> | ||
Revision as of 21:19, 1 May 2020
Problem
If is a constant such that
and
, then for each positive integer
,
equals
Solution
Multiply both sides by and rearrange to
. Using the quadratic equation, we can solve for
. After some simplifying:
Substituting this expression in to the desired gives:
Using DeMoivre's Theorem:
Because is even and
is odd:
Which gives the answer